Towards customer-driven management in hospitality education: A case study of the Higher Hotel Institute, Cyprus - Varnavas, Andreas; Soteriou, Andreas (My University, 2002)
Applying total quality management (TQM) principles in education still remains a great challenge. This paper focuses on hospitality education. Although anecdotal evidence on successful TQM implementation in various hotels can be easily found, no formal approaches on how to implement TQM to the hospitality educational process have appeared in the literature. The Higher Hotel Institute, Cyprus, has recently embarked towards the establishment of a customer-driven management culture. The paper presents and discusses the approach taken by the Institute in collecting and using service quality-related information from three principal groups: namely, future employers, staff and students, towards this goal. Future research directions are also discussed.
Keywords: Education; Hospitality industry; Service quality